Stomach Content Analysis of Hemibagrus nemurus from the Kampar Kiri River, Mentulik Village, Kampar Kiri Hilir District Kampar Regency, Riau Province - Reni Agustin; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTHemibagrus nemurusis one of freshwater fish that inhabit the Kampar Kiri River. This research aims to determine type of food present in the fish’s stomach. To understand the type of food consumed by H. nemurus, a research has been conducted in July to August 2019. Sampling was conducted 4 times, once/ 2 weeks for a two months period. The fish was captured using nets. There were  65 fishes captured, but only   47 fish have full stomach. The analysis was conducted using a gravimetric method. Stomach contents was analysis as a basis to calculate the  Preponderance Index (PI). Results shown that the main food of H. nemurus is fish (PI 67%), the complementary food is plant remains (PI 13%), unidentified debris (PI 13%) and insect (PI 5%), While the additional food is crustacean (PI 2%). Data obtained indicate that H. nemurus is a carnivorous fish. Keyword: Catfish, Feeding Habit, Preponderance Index, Gravimetric Method